Effects of latitudinal variation on field and common garden comparisons between native and introduced groundsel (Senecio vulgaris) populations. (22nd December 2020) - Zhu, Bi-Ru; Li, Xiao-Meng; Zhang, Da-Yong; Liao, Wan-Jin
Abstract: Aims: Field and common garden comparisons are commonly performed to test the rapid evolution of increased vigor in introduced plant populations. Latitudinal clines in phenotypic traits can obscure such evolutionary inferences, particularly when native or introduced populations are distributed across large geographic ranges. We tested whether the latitudinal clines influence comparisons between introduced and native populations of Senecio vulgaris . Methods: Senecio vulgaris is native to Europe but has been introduced in northeastern and southwestern China. To evaluate the performance in terms of growth and reproduction between native European populations and introduced Chinese populations, we compared plant height, number of branches and number of capitula in field populations in native and introduced ranges and in a common garden in Switzerland. Important Findings: The introduced Chinese populations performed better than the native European populations in the field in terms of plant height and number of capitula, which was consistent with the prediction of the evolution of the increased competitive ability (EICA) hypothesis. The Chinese populations produced more capitula than the European populations when the latitudinal cline was considered in the common garden comparison. When we compared the traits of the northeastern Chinese, southwestern Chinese and European populations in both the field and common garden, the northeastern Chinese populations, at latitudes similar to those of the European populations, exhibited greater plant size and more capitula than the European populations in both the field and common garden. However, the southwestern Chinese populations, at latitudes much lower than those of the European populations, did not perform better than the native populations in terms of reproduction. In conclusion, our results suggest that latitudinal clines in phenotypic traits should be considered in field and common garden comparisons when introduced populations are geographically structured.